Analisis Penilaian Keterampilan Menulis Karangan Narasi Menggunakan Media Visual pada Siswa Kelas V SDN Kalideres 06 Pagi - Magdalena, Ina; Nurjamilah, Putri; Ramadhanty, Salwa; Sarah, Sarah (MASALIQ, 2023)
This study aims to analyze the assessment of skills in writing narrative essays using visual media in fifth grade students at SDN Kalideres 06 Pagi. Regarding the skills of writing narrative essays, there are many obstacles faced by students, especially in expressing their ideas or thoughts in written form, students' lack of interest in reading, difficulties in determining the object of writing, difficulty in arranging the right words in standard language, and thinking that writing is something which is unpleasant. Therefore, the solution to overcome these obstacles is by using visual media because it can attract students' understanding to be skilled at writing narrative essays. This type of research used is qualitative research with descriptive methods. Data collection techniques in the form of observation, interviews, documentation, and test. The research subjects were teachers and students of grade V. The results obtained in this study were that students achieve the highest score of 90 and the lowest score of 55, it is important for students to increase their scores. In assessing the teacher gives scores according to indicators in writing using visual media including conformity with pictures, accuracy of the meaning of the whole story, and accuracy (words, sentences, spelling, and grammar).